Epidemiological trends of hand osteoarthritis from 1990 to 2019: Estimates from the 2019 Global Burden of Disease study - Wan, Junlai; Qian, Xiaoyuan; He, Zhiyi; Zhu, Ziqing; Cheng, Peng; Chen, Anmin (Frontiers in Medicine, 2022)
Background: Hand osteoarthritis (OA) is a chronic progressive disease characterized by disabling hand pain, with a high clinical burden. Here, this study was designed to assess the epidemiological patterns of hand OA and analyze its secular trends from 1990 to 2019 based on sex, age, and socio-demographic index (SDI) at global, regional, and national levels. Methods: Data on the incidence and disability-adjusted life years (DALYs) of hand OA were extracted from the 2019 Global Burden of Disease (GBD) and their respective age-standardized rates (ASR) were calculated. The estimated annual percentage changes (EAPCs) of ASR were calculated to assess the prevalent trends of the incidence and DALYs of hand OA over the past decades. The relationship between ASR and SDI was analyzed by Pearson’s correlation analysis. Results: The incident cases of hand OA increased from 371.30 million in 1990 to 676.02 million in 2019, increasing by 82.07%, whereas its age-standardized incidence rate (ASIR) decreased, with a downward trend (EAPC = -0.34; 95% confidence interval [CI]: -0.39– -0.28). Before 70 years, with the changes of age, the incidence of hand OA with a unimodal distribution was observed, peaking at 50−54 years, yet its incidence was an upward trend distributed in the >70 years age groups. Similarly, hand OA-related DALYs increased in the past 30 years. Meanwhile, its annual age-standardized DALYs rate also decreased, with EAPCs of -0.35 (95% CI, -0.38 – -0.32). The DALYs increased with age. In 2019, the ASIR and age-standardized DALYs rate were positively associated with the SDI regions. The incidence and DALYs presented female predominance. The burden of hand OA displayed obvious geographical diversity over the past three decades. Conclusion: The incident cases of hand OA increased globally from 1990 to 2019, while the ASIR and age-standardized DALYs rate decreased over the past decades. However, in many countries and regions, a rising trend of ASR related to incidence and DALYs is observed. In addition, the prevalence revealed geographical, sex, and age diversity. Thus, governments and medical institutions should reallocate medical resources based on the epidemiological characteristics of hand OA.